Prediction of safety and effectiveness of a candidate biocontrol agent : quarantine evaluation of the root-feeding, Mexican flea beetle, Longitarsus bethae, for potential release against the noxious weed, Lantana camara, in Africa - Simelane, David Okhi (Department of Biological Sciences, 2014)
Includes bibliographical references (leaves 151-173).